Patterns of tau pathology identified with 18F‐MK‐6240 PET imaging. Issue 2 (31st May 2021) - Kreisl, William Charles; Lao, Patrick J.; Johnson, Aubrey; Tomljanovic, Zeljko; Klein, Julia; Polly, Krista; Maas, Benjamin; Laing, Krystal K.; Chesebro, Anthony G.; Igwe, Kay; Razlighi, Qolamreza R.; Honig, Lawrence S.; et al.
Abstract: Introduction: Positron emission tomography (PET) imaging for neurofibrillary tau allows investigation of the in vivo spatiotemporal progression of Alzheimer's disease (AD) pathology. We evaluated the suitability of 18 F‐MK‐6240 in a clinical sample and determined the relationships among 18 F‐MK‐6240 binding, age, cognition, and cerebrospinal fluid (CSF)‐based AD biomarkers. Methods: Participants (n = 101, 72 ± 9 years, 52% women) underwent amyloid PET, tau PET, structural T1‐weighted magnetic resonance imaging, and neuropsychological evaluation. Twenty‐one participants had lumbar puncture for CSF measurement of amyloid beta (Aβ)42, tau, and phosphorylated tau (p‐tau). Results: 18 F‐MK‐6240 recapitulated Braak staging and correlated with CSF tau and p‐tau, normalized to Aβ42 . 18 F‐MK‐6240 negatively correlated with age across Braak regions in amyloid‐positive participants, consistent with greater tau pathology in earlier onset AD. Domain‐specific, regional patterns of 18 F‐MK‐6240 binding were associated with reduced memory, executive, and language performance, but only in amyloid‐positive participants. Discussion: 18 F‐MK‐6240 can approximate Braak staging across the AD continuum and provide region‐dependent insights into biomarker‐based AD models.